Berlin i Niemcy w dwóch adaptacjach filmowych powieści Alfreda Döblina Berlin Alexanderplatz - Nowakowski, Jacek (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The subject of this paper is the image of Berlin and Germany that emerges from two film adaptations of the novel Berlin Alexanderplatz. The first one, a 1980 TV series by Rainer Werner Fassbinder, closely follows the letter and spirit of the original 1929 novel; we see a faithful recreation of the material world and the mindset of German society in the final years of the Weimar Republic. In the second one, a 2021 cinema production by Burhan Qurbani, the plot is modernised. The main context of the film is the plight of refugees and economic migrants in contemporary Germany and the problems portrayed are linked to issues of race and post-colonialism.